Involvement of Histone Lysine Crotonylation in the Regulation of Nerve-Injury-Induced Neuropathic Pain - Zou, Yu; Bai, Xue-Hui; Kong, Ling-Chi; Xu, Fei-Fei; Ding, Ting-Yu; Zhang, Peng-Fei; Dong, Fu-Lu; Ling, Yue-Juan; Jiang, Bao-Chun (Frontiers in Immunology, 2022)
Histone lysine crotonylation (KCR), a novel epigenetic modification, is important in regulating a broad spectrum of biological processes and various diseases. However, whether KCR is involved in neuropathic pain remains to be elucidated. We found KCR occurs in macrophages, sensory neurons, and satellite glial cells of trigeminal ganglia (TG), neurons, astrocytes, and microglia of the medulla oblongata. KCR was detected mainly in small and medium sensory neurons, to a lesser extent in large neurons. Peripheral nerve injury elevated KCR levels in macrophages in the trigeminal and dorsal root ganglia and microglia in the medulla oblongata but reduced KCR levels in sensory neurons. Inhibition of histone crotonyltransferases (p300) by intra-TG or intrathecal administration of C646 significantly alleviated partial infraorbital nerve transection (pIONT)- or spinal nerve ligation (SNL)-induced mechanical allodynia and thermal hyperalgesia. Intra-TG or intrathecal administration of Crotonyl coenzyme A trilithium salt to upregulate KCR dose-dependently induced mechanical allodynia and thermal hyperalgesia in mice. Mechanismly, inhibition of p300 alleviated pIONT-induced macrophage activation and reduced the expression of pain-related inflammatory cytokines Tnfα, Il1β and chemokines Ccl2 and Cxcl10. Correspondingly, exogenous crotonyl-CoA induced macrophage activation and the expression of Tnfα, Il1β, Il6, Ccl2 and Ccl7 in TG, which C646 can repress. These findings suggest that histone crotonylation might be functionally involved in neuropathic pain and neuroinflammation regulation.